Numerical Studies on Flow Behavior of Composite Propellant Slurry During Vacuum Casting - Bejoy Thiyyarkandy (Journal of Aerospace Technology and Management, 2012)
This work has presented the first stage performance at design and off-design operating points of an axial turbine, with two stages using a numerical simulation. Experimental methods of predicting the performance of axial turbine is costly and time consuming compared to the computational fluid dynamics approach. Therefore, computational techniques were adopted to determine the stage performance. This study analyzed the first stage performance of an axial flow turbine, using a computational tool for simulating the steady state two/three-dimensional viscous flow. A computational fluid dynamics software was used to solve the rans equations with the spalart-allmaras turbulence model. The computational fluid dynamics results were compared with those obtained from the mean line loss model code. The comparisons have been conducted to provide a pretest performance for the turbine first stage.